Assessing the internal audit practices in Ghana Education Service –Brong Ahafo Region. - Brobbey, Isaac (KNUST, 2025)
A Thesis Submitted In Partial Fufilment Of The Requirement For The Award Of The Degree Of Master Of Business Administration Department Of Accounting And Finance.